Complete mineralization of a humic acid by SO4·− generated on CoMoO4/gC3N4 under visible-light irradiation. (4th April 2019) - Gao, Zhao; Yang, Hanpei; Cao, Yang; Wu, Qiangshun; Kang, Li; Mao, Jingtao; Wu, Junming
Abstract: The sulfate radical ( SO 4 · − ), almost a most active species, is believed to be the best oxidant in the elimination of aquatic organics in advanced oxidation processes. However, acquiring their steady-state generation with high concentration is still challenging work. In this report, we focused on designing a novel composite, in which uniform and rod-like CoMoO4 was fabricated on gC3 N4 through Co–N coordination. In this way, the composite acquired an immobilization of Co (II) in its refraining from leaking, and synchronically, a dense heterojunction between CoMoO4 and gC3 N4 . Over the heterojunctions, photogenerated electrons gained a prolonged lifetime through their efficient separation from holes. The life-prolonged electrons, together with Co (II) in CoMoO4, effectively activated the persulfate, and a concentration of steady-state SO 4 · − as high as 1.8 × 10 −14 mol · l −1 was obtained. With SO 4 · − fast and complete mineralization of a humic acid was achieved.